Leibniz: What Kind of Relationalist? - Lochmanová, Kateřina (Teorie vědy / Theory of Science, 2019)
In this paper, I am trying to challenge the mainstream interpretation of Leibniz’s metaphysics of space, introduced in his letters to an English scholar Samuel Clarke. Based on the correspondence with Clarke, Leibniz’s metaphysics of space is usually considered to be a sharp counterpart to Clarke’s as well as Newton’s one. However, in this paper I am pointing out that this interpretation becomes untenable, especially considering Leibniz’s geometry called “analysis situs”. Leibniz did not defend a typically relational conception of space.